PARENTAL CHALLENGES: MENTAL HEALTH OUTCOMES AMONG PARENTS OF CHILDREN WITH INTELLECTUAL DISABILITIES (Contemporary Journal of Social Science Review, 2025)
The relationship between parental mental health outcomes, specifically stress, anxiety, and depression, has been widely examined in international research; however, limited evidence exists within the Pakistani context, particularly among parents of children with intellectual disabilities. The present study aimed to address this gap by exploring the relationships between stress, anxiety, and depression and examining the mediating role of anxiety. Using a cross-sectional correlational design, data were collected through purposive sampling from 180 parents (mothers and fathers) of children under 18 years diagnosed with intellectual disabilities. The Depression, Anxiety, and Stress Scale (DASS-21) was administered, and analyses were conducted using IBM SPSS version 26. Results revealed significant positive associations among stress, anxiety, and depression, with anxiety partially mediating the relationship between stress and depression. The findings highlight the need for parental counseling, mental health support programs, and affordable special education facilities to improve family well-being.